Complex reaction processes in combustion unraveled by neural network-based molecular dynamics simulation - Jinzhe Zeng (Nature Portfolio, 2020)
Gaining insights into combustion processes is challenging due to the complex reactions involved. The present work proposes a neural network potential model trained to ab initio data that enables to simulate the combustion of methane by predicting reactants, products and reaction intermediates.